2015
DOI: 10.1007/s00894-015-2772-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparative molecular dynamics study of thermophilic and mesophilic β-fructosidase enzymes

Abstract: Arabidopsis thaliana cell wall invertase 1 (AtcwINV1) and Thermotoga maritima β-fructosidase (BfrA) are among the best structurally studied members of the glycoside hydrolase family 32. Both enzymes hydrolyze sucrose as the main substrate but differ strongly in their thermal stability. Mesophilic AtcwINV1 and thermophilic BfrA have divergent sequence similarities in the N-terminal five bladed β-propeller catalytic domain (31 %) and the C-terminal β-sandwich domain (15 %) of unknown function. The two enzymes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…The RMSD and RMSF values of EmcMDH were highly preserved during simulation at different temperatures, whereas the values for more heat-sensitive ErcMDH increased with temperature. The difference in structural thermal sensitivity between the EmcMDH and ErcMDH orthologs is consistent with the temperature adaptation observed in β-fructosidase of T. maritima (Mazola et al, 2015). The active site geometry of this thermophilic β-fructosidase was strongly conserved during simulations at different temperatures, whereas an increase in RMSD value was observed for a mesophilic ortholog at elevated temperature.…”
Section: Simulations: Linking Structure To Functionsupporting
confidence: 81%
See 1 more Smart Citation
“…The RMSD and RMSF values of EmcMDH were highly preserved during simulation at different temperatures, whereas the values for more heat-sensitive ErcMDH increased with temperature. The difference in structural thermal sensitivity between the EmcMDH and ErcMDH orthologs is consistent with the temperature adaptation observed in β-fructosidase of T. maritima (Mazola et al, 2015). The active site geometry of this thermophilic β-fructosidase was strongly conserved during simulations at different temperatures, whereas an increase in RMSD value was observed for a mesophilic ortholog at elevated temperature.…”
Section: Simulations: Linking Structure To Functionsupporting
confidence: 81%
“…Previous studies of proteins of thermophilic organisms have shown that these species' proteins are characterized by high thermal stability and low levels of structural fluctuation in MD simulation studies (Li et al, 2005). For example, the equilibrium RMSD value of thermophilic isopropylmalate dehydrogenase from Thermus thermophilus was 3.5 Å at 64°C (Sharma and Sastry, 2015); the thermophilic β-fructosidase from Thermotoga maritima reached the stable state with a value of 1.97 Å at 80°C (Mazola et al, 2015). The hyperthermophilic amylase from Bacillus licheniformis is thermostable at very high temperature; the native state of the protein and enzymatic activity is strongly conserved at temperature below 90°C, whereas 50% of the molecules are unfolded at 103°C (Fitter et al, 2001;Fitter and Haber-Pohlmeier, 2004;Fitter, 2005).…”
Section: Simulations: Linking Structure To Functionmentioning
confidence: 99%
“…Solvent-accessible surface area (SASA) is the surface area of a molecule that interacts with the solvent molecules (Mazola et al, 2015 ). The average SASA values for the LasR, LasR–bakuchiol, Rh1R, and Rh1R–bakuchiol complexes were calculated using the gmx sasa module of GROMACS.…”
Section: Resultsmentioning
confidence: 99%
“…Solvent accessible surface area (SASA) of a protein is the area that directly interacts with its surrounding solvent [38,39]. The SASA of a protein is directly interrelated to its R g .…”
Section: Hydrogen Bonds Analysismentioning
confidence: 99%